2012
DOI: 10.1172/jci60659
|View full text |Cite
|
Sign up to set email alerts
|

Cross-presenting CD103+ dendritic cells are protected from influenza virus infection

Abstract: CD8 + cytotoxic T cells are critical for viral clearance from the lungs upon influenza virus infection. The contribution of antigen cross-presentation by DCs to the induction of anti-viral cytotoxic T cells remains controversial.Here, we used a recombinant influenza virus expressing a nonstructural 1-GFP (NS1-GFP) reporter gene to visualize the route of antigen presentation by lung DCs upon viral infection in mice. We found that lung CD103 + DCs were the only subset of cells that carried intact GFP protein to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
228
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(242 citation statements)
references
References 42 publications
12
228
2
Order By: Relevance
“…5). It is likely that the disappearing CD11c ϩ cells are dendritic cells which migrate to draining lymph nodes soon after contact with viral antigen, as recently demonstrated by others (30,31). Those authors further demonstrated that the migratory dendritic cells were not productively infected with influenza virus, which explains why IFN production by these cells was not inhibited by virus-encoded NS1.…”
Section: Cd11cmentioning
confidence: 60%
“…5). It is likely that the disappearing CD11c ϩ cells are dendritic cells which migrate to draining lymph nodes soon after contact with viral antigen, as recently demonstrated by others (30,31). Those authors further demonstrated that the migratory dendritic cells were not productively infected with influenza virus, which explains why IFN production by these cells was not inhibited by virus-encoded NS1.…”
Section: Cd11cmentioning
confidence: 60%
“…In the presence of inflammatory cytokines released from the lung epithelium and inflammatory cells, e.g. those produced by inflammasome (IL-1β and IL-18) or granulocyte-macrophage colony-stimulating factor (GM-CSF) [110][111][112][113], they are induced to migrate to the draining lymph nodes. In the lymph nodes, CD103 + DCs serve as potent antigen-presenting cells for the activation of naïve CD8 + and CD4 + T-cells and for the presentation of viral antigens to rare virus-specific memory T-cells required for adaptive immunity [114,115].…”
Section: Molecular and Cellular Interactions At The Virus-host Interfacementioning
confidence: 99%
“…8,9,37 Antigen uptake represents an important factor that can modulate antigen presentation. CD103 1 DCs take up antigens less efficiently than CD103 -DCs.…”
Section: Icd103-dcs Cross-present Cell-associated Antigensmentioning
confidence: 99%
“…37 Notably, iCD103-DCs and GM-DCs also cross-present cell-associated OVA, albeit with slightly reduced efficiency compared with lung CD103…”
Section: Icd103-dcs Cross-present Cell-associated Antigensmentioning
confidence: 99%